Education Project Based Learning in Engineering Students as Character Development - Iasya, Sarah; Prajna Vashti, Respati; Dachlan, Rita Farida (Jurnal Sosial Humaniora, 2024)
The formation of student character through integration between courses that are collected through the Project Based Learning (PjBL) learning strategy. The PjBL method directs students to be critical and work together in order to solve problems. The study used a quantitative descriptive method, data was obtained through interviews with PjBL teachers and questionnaires to students. because it describes the situation that occurs, systematically and factually with the aim of analyzing data by describing or depicting the data that has been collected as a solution to the research problem. The focus of this study is the aspect of attitude, self-confidence, and cooperation. The results of the study are as follows: in carrying out the project, students have shown attitudes and ethics in accordance with the values ​​of Pancasila as one of the courses with the project learning method, students also show a sense of responsibility during the project. Students show a more confident attitude when having to communicate with the PjBL management, in addition, students are more confident when presenting because as many as 84.6%, students understand the material and practice presentations. As many as 76.9% of students agree that cooperation is carried out by assigning work based on the expertise and strengths of each team member 76.9%. Thus, project based learning is proven to be able to develop the character of engineering students.